ANALISA KINERJA LALU LINTAS RUAS JALAN SEMARANG – GROBOGAN PADA PERSIMPANGAN PASAR KARANGAWEN KABUPATEN DEMAK - Hidayat, Muhammad Mansur; Aprillianto, Hery; Rizani, Mohammad Debby; Ariawan, Donny (Jurnal Teknik Sipil Giratory UPGRIS, 2022)
ABSTRACT. This type of research is quantitative research. The problems in this study are 1) The factors that cause traffic jams on the Semarang-Grobogan Karangawen Demak road. 2) the performance of the unsignalized intersection on the Semarang-Grobogan Karangawen Demak road. This type of research is quantitative research. Based on the analysis, the results for side resistance are 1215.2 vehicles/hour for the east direction and 1162.7 vehicles/hour for the west direction, so the side resistance class for the east and west directions is very high (VH) because the total weight is greater than 900 vehicles/hour with conditions of commercial areas and high activity on the side of the road. The level of congestion with traffic volume in the west is 3122 pcu/hour and 1686 pcu/hour in the east and a capacity of 1469.52 pcu/hour for the west and east and the degree of saturation is 0.87 for the west and 0.54 for the east direction east.Keywords: factors causing congestion, performance of unsignalized intersections.